Evolution of Epiphytism and Fruit Traits Act Unevenly on the Diversification of the Species-Rich Genus Peperomia (Piperaceae) - Frenzke, Lena; Goetghebeur, Paul; Neinhuis, Christoph; Samain, Marie-Stéphanie; Wanke, Stefan (Frontiers in Plant Science, 2016)
The species-rich genus Peperomia (Black Pepper relatives) is the only genus among early diverging angiosperms where epiphytism evolved. The majority of fruits of Peperomia release sticky secretions or exhibit hook-shaped appendages indicative of epizoochorous dispersal, which is in contrast to other flowering plants, where epiphytes are generally characterized by fruit morphological adaptations for anemochory or endozoochory. We investigate fruit characters using Cryo-SEM. Comparative phylogenetic analyses are applied for the first time to include life form and fruit character information to study diversification in Peperomia. Likelihood ratio tests uncover correlated character evolution. We demonstrate that diversification within Peperomia is not homogenous across its phylogeny, and that net diversification rates increase by twofold within the most species-rich subgenus. In contrast to former land plant studies that provide general evidence for increased diversification in epiphytic lineages, we demonstrate that the evolution of epiphytism within Peperomia predates the diversification shift. An epiphytic-dependent diversification is only observed for the background phylogeny. An elevated frequency of life form transitions between epiphytes and terrestrials and thus evolutionary flexibility of life forms is uncovered to coincide with the diversification shift. The evolution of fruits showing dispersal related structures is key to diversification in the foreground region of the phylogeny and postdates the evolution of epiphytism. We conclude that the success of Peperomia, measured in species numbers, is likely the result of enhanced vertical and horizontal dispersal ability and life form flexibility but not the evolution of epiphytism itself.